Benefits of the Use of ICT Services Perceived by Farmers for Acquiring Agricultural Information in Central U.P. - Mishra, Abhishek; Yadav, O P; Yadav, Vishakha; Mishra, Siddhant; Kumar, Naveen (Indian Journal of Extension Education, 2020)
ICT services are yet to make any breakthrough in agricultural information dissemination and other areas. There are many information servers available in online communication services at grass root levels; some of them liketelephone, computer, internet, and other ICT services are more effective for the transfer of agricultural technologies. ICT can help an average Indian farmer to get relevant information regarding agro-inputs, crop production technologies, agro-processing, market support, agro-finance and management of farm agri-business. Therefore, an attempt has been made to find out the benefits of the use of ICT services perceived by farmers for acquiring agricultural information. So, six villages from the Bakshi ka Talab block in the Lucknow district in 2018 was surveyed using a randomized survey with a questionnaire and interview schedule with a sample of 20 respondents from each village. Out of the 120 respondents, the study revealed that ICT tools like radio 51.67 per cent as low, T.V. 48.33 per cent as a medium, Mobile phone 51.67 per cent as medium, Internet 47.50 per cent as medium, Social media 48.33 percent as low level of benefits perceived by respondents respectively. It is concluded the there is a need for improving the awareness and infrastructure of ICT tools in rural areas.